2011
DOI: 10.1021/jp2001964
|View full text |Cite
|
Sign up to set email alerts
|

Structural Dynamics of the S4 Voltage-Sensor Helix in Lipid Bilayers Lacking Phosphate Groups

Abstract: Voltage-dependent K+ (Kv) channels require lipid phosphates for functioning. The S4 helix, which carries the gating charges in the voltage-sensing domain (VSD), inserts into membranes while being stabilized by a protein-lipid interface in which lipid phosphates play an essential role. To examine the physical basis of the protein-lipid interface in the absence of lipid phosphates, we performed molecular dynamics (MD) simulations of a KvAP S4 variant (S4mut) in bilayers with and without lipid phosphates. We find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…Strong H-bonding interactions with the lipid’s phosphate moiety have profound implications on the molecular organization of membrane-active compounds. For example, it has been shown that a lipid’s phosphate moiety plays important roles in orchestrating membrane insertion of arginine monomers 48 , anchoring of the antimicrobial peptide protegrin-1 49 , and regulating the voltage-gated potassium channel 50 . In ether bilayers, the prevalent association of OH-Chol with the phosphate oxygen also reduces the hydration level near the phosphate, as the interfacial water molecules that normally associate with the phosphate oxygen are displaced by the OH-Chol.…”
Section: Discussionmentioning
confidence: 99%
“…Strong H-bonding interactions with the lipid’s phosphate moiety have profound implications on the molecular organization of membrane-active compounds. For example, it has been shown that a lipid’s phosphate moiety plays important roles in orchestrating membrane insertion of arginine monomers 48 , anchoring of the antimicrobial peptide protegrin-1 49 , and regulating the voltage-gated potassium channel 50 . In ether bilayers, the prevalent association of OH-Chol with the phosphate oxygen also reduces the hydration level near the phosphate, as the interfacial water molecules that normally associate with the phosphate oxygen are displaced by the OH-Chol.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to POPA and CHOL, positively charged lipid DOTAP has been shown to inhibit KvAP gating (7,8,11). MD simulations reveal that DOTAP lipids move away from the S4 helix because of the repulsive interactions between the positive charges on the DOTAP and the S4 segment (47). Furthermore, higher water penetration was observed in the S4 vicinity (47).…”
Section: Electromechanical Model Predicts Dotap-mediated Inhibition Omentioning
confidence: 99%
“…MD simulations reveal that DOTAP lipids move away from the S4 helix because of the repulsive interactions between the positive charges on the DOTAP and the S4 segment (47). Furthermore, higher water penetration was observed in the S4 vicinity (47). We employed our electromechanical continuum model to quantify the consequences of these findings on channel gating.…”
Section: Electromechanical Model Predicts Dotap-mediated Inhibition Omentioning
confidence: 99%
“…The issue of convergence has been rectified in part by running several long simulations and using non-equilibrium sampling method or steered MD to calculate the observables of interest. A series of extended simulations (~100 ns) on the voltage sensor domain of potassium channels revealed the importance of lipid phosphates in accommodating the significantly charged S4 helix [22]. Using umbrella sampling, potential of mean force has been calculated for permeation and effect of a potassium ion on the second ion passing through gramicidin A channel [23].…”
Section: Bioinformatics -Updated Features and Applications 86mentioning
confidence: 99%